Pengembangan Media Pembelajaran Berbantuan Lectora Inspire dan Plotagon pada Materi SPLDV untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Setiawan, Muhamad Nur; Fatahillah, Arif; Adawiyah, Robiatul (Jurnal Tadris Matematika, 2023)
This research aims to describe the process and results of the development of learning media with 3D characters assisted by Lectora Inspire and Plotagon software to improve student's critical thinking skills in the material of systems for solving systems of linear equations in two variables. This research uses research and development methods with a 4D development model. This development model consists of four stages, namely definition, design stage, development stage, and dissemination stage. The learning media developed must meet the feasibility requirements, namely valid, practical, and effective. The results of this research show that the average validity value of the 3 validators is 90% and is included in the valid category. The level of practicality of learning media is 92% based on user questionnaire responsses and is included in the practical category. The level of effectiveness is determined based on the N-Gain results of 28 students who took the pretest and posttest with a percentage result of 79% so it is in the effective category. Based on these results, the learning media developed was proven to be valid, practical, and effective in improving students' critical thinking skills.